Utilizing Artificial Intelligence to Optimize Public Services: A Case Study in Regional Government - Isra Muksin; Mansyur Djamal (Technologia Journal, 2025)
This study aims to analyze the use of Artificial Intelligence (AI) to optimize public services in local governments, while identifying challenges and opportunities for its implementation. The research method used is a qualitative case study approach, through in-depth interviews, observations, and documentation analysis. The results show that the application of AI through service chatbots, digital queuing systems, and population data analysis can improve bureaucratic efficiency, reduce public waiting times, and increase public satisfaction. However, AI implementation still faces challenges such as limited infrastructure, lack of human resource competency, resistance from some employees, and public doubts about data security. This study confirms that the success of AI adoption in local governments is determined not only by technological readiness, but also by data protection policies, change management, and increasing public digital literacy.